2008
DOI: 10.1002/cne.21872
|View full text |Cite
|
Sign up to set email alerts
|

Expression and developmental regulation of oxytocin (OT) and oxytocin receptors (OTR) in the enteric nervous system (ENS) and intestinal epithelium

Abstract: Although oxytocin (OT) and oxytocin receptor (OTR) are known for roles in parturition and milk let-down, they are not hypothalamus-restricted. OT is important in nurturing and opposition to stress. Transcripts encoding OT and OTR have been reported in adult human gut, and OT affects intestinal motility. We tested the hypotheses that OT is endogenous to the enteric nervous system (ENS) and that OTR signaling may participate in enteric neurophysiology. Reverse transcriptase polymerase chain reaction confirmed OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 87 publications
7
137
0
Order By: Relevance
“…The rationale for studying OT signaling in gut cells stems from our prior work showing that the OTR is highly expressed in enterocytes of newborn rats during their suckling period (Welch et al 2009). Those studies showed that after weaning, OTR expression declined in the fully developed villi and appeared at the crypt villus junction and at the newly developed crypts, as well as in cell adherens junctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for studying OT signaling in gut cells stems from our prior work showing that the OTR is highly expressed in enterocytes of newborn rats during their suckling period (Welch et al 2009). Those studies showed that after weaning, OTR expression declined in the fully developed villi and appeared at the crypt villus junction and at the newly developed crypts, as well as in cell adherens junctions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OT may act differently at various stages of development. In the context of a transient high level OTR expression in enterocytes of postnatal rat pups (Welch et al 2009), OT may be instrumental in protection of enterocytes against the cellular ER stress involved in intense developmental differentiation of colonic surface and small intestine villus structure. Later in life, these biological mechanisms may be redirected to regulate inflammatory responses in the gut.…”
Section: S65mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of the OT receptor (OTR) in both the neurons of the enteric nervous system and intestinal epithelial cells (Welch et al, 2009) led to a systematic examination of gut OT and OTR signalling. OT was found to play an important role in gut development and function.…”
Section: Visceral Oxytocin and Emotional Behaviormentioning
confidence: 99%
“…Thus, central OXT plays a predominant role in regulating stress-induced GI dysmotility. Although OXT and its receptors are expressed on the smooth muscle cells, enteric neurons and intestinal epithelium of the GI tract [19] , peripheral OXT may not have a major role in attenuating stress responses. 1-3.…”
mentioning
confidence: 99%